Variation of surface radio-refractivity at New Delhi (MAUSAM, 1974)
Studies carried out in temperate latitudes indicate that a significant relation exists between the signal strength of microwave communication systems and the variations in surface radio refractivity (Ns). With the expansion of microwave communication and television in India, communication engineers are vitally concerned in finding the extent of Variation in Ns in the country. To this end, Ns values for four representative months have been calculated In respect of New Delhi, (Safdarjung) based on ten years monthly mean data for six synoptic hours. A comparison with corresponding Ns values at New Delhi Palam has also been made to bring out the Importance of proper site selection. The most significant feature of the analysis is the year round diurnal range of 20 N Units or less accompanied by a strong seasonal range of about 70 N units in surface radio-refractivity. An attempt has been made to relate these changes with climatological features and to assess their likely effect on signal strength.